Manajemen Pemasaran Bank Syariah di Era Digital - Gladys Elysia Valmai; Ade Lina Br. Sihombing; Nazwa Aurelia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The rapid development of digital technology has significantly influenced marketing strategies in Islamic banking in Indonesia. Despite the growth of Islamic banks, challenges remain in implementing effective marketing management that is aligned with Islamic principles while adapting to digital transformation. This study aims to analyze the role of digital marketing in Islamic bank marketing management and to identify the opportunities and challenges faced in its implementation. The research method used is a literature study by reviewing relevant national journals related to Islamic banking marketing and digital marketing strategies. The results show that digital marketing contributes to improving marketing effectiveness, expanding market reach, and strengthening customer trust in Islamic banks through transparent and informative communication. However, challenges such as inconsistency in applying Islamic values in digital marketing content, data security issues, and limited human resource competence remain significant concerns. In conclusion, digital marketing has strong potential to support Islamic bank marketing management, provided that its implementation consistently adheres to Islamic principles and is supported by adequate human resources and digital infrastructure.